The Effectiveness and Safety of Percutaneous Cystolithotripsy for Vesicle Calculus in Children: A Single-Center Study - Samiullah Opal. Kifayat Tariq. Sikandar Hayat, Ihsanullah Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Primary bladder stones are common among children from developing countries but may be difficult to cure. Transurethral cystolithotripsy, open cystolithotomy, and shock wave lithotripsy are the treatment modalities for vesical calculi in children. Transurethral lithotripsy is less efficient in children because of the small caliber of the urethra. PCCL is a less intrusive and efficient procedure for removing bladder stones in pediatric patients. Objectives: The objective of the study was to determine the safety and efficacy of PCCL in children with bladder stones in third-world nations. Materials and Methods: There was a search for( PCCL) in pediatric individuals diagnosed with vesical calculus. 90% male and 10% female total of 120 patients enrolled in the single-center trial at the Department of Pediatric Urology at the Institute of Kidney Diseases between January 2021 to January 2022. The surgery was performed under a general anesthetic. After a thorough inspection, a suprapubic puncture of the lower urinary tract (by cystoscopy) was done. The tract was only dilated up to 14 Fr. The stone was fragmented using pneumatic lithotripsy after passing the nephroscope. After 36 hours per urethral catheter was removed. Results: In this study, the mean age of the patients was 4.2.14 years. The majority of patients were kids. The average gem was 9.3 millimeters in diameter. Successful stone fragmentation and retrieval took place in an average of 40 min. The only major problems seen during or after surgery were hematuria, infection, and moderate mucosal injury; all three were managed conservatively. In 108 out of 120 cases (90%), ammonium acid urate was found to be the primary constituent of the stones and the core. Conclusion: The success rate of percutaneous cystolithotripsy in the treatment of bladder stones in children is higher, and it is ready for immediate use. The operation is quick and causes minimal discomfort. Keywords: Effectiveness, Percutaneous , Cystolithotripsy, Vesical Calculus, Children